Development Of Agriculture On The Basis Of "Green Economy". - Abdikarimova Aynura Abay qizi (Zien Journals, 2024)
In this article, the development of the agricultural sector on the basis of ecological requirements, the possibilities of meeting the growing needs of the population for food products, minimizing the level of environmental degradation associated with certain methods of agricultural management, and solving the problem of poverty in rural areas. explained about.
Keywords: Green economy; Decoupling; green technologies